Prevalence of Autism in Children Prenatally Exposed to Alcohol: A Pilot Study. (1st June 2016) - Young, E; Stade, B; Falsetti, A; Fulford, E; Jegathesan, T
Abstract: BACKGROUND: The prevalence of autism among Canadian children is 1.1 in 100.1 The possibilty of an association between prenatal alcohol exposure and autism was based on early case reports describing autistic behaviour in children with Fetal Alcohol Syndrome.2 OBJECTIVES: The objective of this study was to identify the prevalence of autism in children prenatally exposed to alcohol. DESIGN/METHODS: A chart review was conducted of 220 children, aged 4 to 16 years, admitted to a Fetal Alcohol Spectrum Disorder(FASD) Clinic, and prenatally exposed to alcohol. Descriptive statistics were used to determine prevalence of the autism diagnosis, number of children diagnosed with FASD, and relevant demographic data. RESULTS: Nine (9) of the total 220 children, or 4.1 %, had been diagnosed with autism using standarized tests. Mean age was 7.6 years with a range of 4.3 to 14.2 years. Five (5) of the children were boys, and 4 were girls. Six (6) additional children had autistic behaviours: autism was ruled out in 2 of the 6 children, and 4 had not been assessed. Eight (8) of the 9 children diagnosed with autism were also diagnosed with FASD, and in 1 child the diagnosis was deferred. CONCLUSION: The prevalence of autism among children prenatally exposed to alcohol was significantly higher than the overall Canadian population (4.1 % vs. 1.1 %). Implications for practice and research are described.